Nigeria Normative Data for Defining Glaucoma in Prevalence Surveys*. (17th March 2015) - Kyari, Fatima; Abdull, Mohammed M.; Sallo, Ferenc B.; Spry, Paul G.; Wormald, Richard; Peto, Tunde; Faal, Hannah B.; Gilbert, Clare E.; ,
ABSTRACT: Purpose : To determine normative values for defining glaucoma in cross-sectional surveys in Nigerian adults. Methods : Multistage stratified cluster random sampling with probability-proportional-to-size procedures to select a nationally representative sample of 15, 027 persons aged ≥40 years in 305 clusters across Nigeria. Systematic sampling of 1 in 7 participants gave 1759 who were examined in detail to construct a normative database. The normative subset was used to determine values for vertical cup/disc ratio (VCDR) and intraocular pressure (IOP) for glaucoma diagnosis according to the International Society of Geographical and Epidemiological Ophthalmology (ISGEO) criteria. Examinations included visual field testing by frequency doubling technology (FDT), Goldmann applanation tonometry, and optic disc image grading by Moorfields Eye Hospital Reading Centre. Results : In the normative dataset, 1057/1759 persons (60.1%) had normal FDTs, and constituted the hypernormal. Of these, 851 had VCDR and 973 had IOP measurements taken in both eyes. For category 1 (structural and functional evidence of glaucoma), the 97.5th percentile VCDR was 0.7. For category 2 (advanced structural damage with unproven visual field loss), the 99.5th percentile VCDR was 0.75. In addition, asymmetry in VCDR was 0.1 difference at the 97.5th percentile and 0.2 difference at the 99.5th percentile. Category 3 criteria were used when the optic disc was not visible and field testing not possible; 99.5th percentile IOP is one criterion (28 mmHg). Conclusion : While these results do not differentiate between open-angle and angle-closure mechanisms, they can be applied to determine the prevalence of glaucoma in Nigeria and sub-Saharan African countries with similar sociodemographic characteristics.